Cannabis-related information sources among US residents: A probability-weighted nationally representative survey - Kevin F. Boehnke; Tristin Smith; Michael R. Elliott; Adrianne R. Wilson-Poe; Daniel J. Kruger (BMC, 2024)
Abstract Introduction The Department of Health and Human Services recently recommended rescheduling cannabis from Schedule I to Schedule III, which might have broad effects on public health outcomes related to cannabis. In this changing environment, understanding national patterns in how people obtain information about cannabis is critical to informing public health outreach and education. Methods We surveyed American adults (≥ 18 years) between June 22nd-26th, 2023 using the AmeriSpeak panel. We assessed past year cannabis use, intentions for cannabis use, and where participants got their information about cannabis. We investigated differences by past year use and explored associations between demographic and cannabis use characteristics with information sources using logistic regression. Results Participants (n = 1,161) were 48.3±27.3 years of age (mean±standard deviation), 51% female, and 27% reported past year cannabis use. The most common information sources used were friends/family (35.6%) and websites (33.7%), while the least common information sources were health/medical care providers (9.3%), employees at place of purchase (8.6%), and government agencies (4.7%). Past year cannabis use was positively associated with all information sources except government agencies and popular media articles. A higher proportion of those using cannabis medically (with or without recreational use) obtained information from a healthcare provider (16.4% vs. 5.2%, p = 0.006). Conclusions As cannabis accessibility increases and legality continues changing, there is a strong need for better clinician education, improved public health outreach, and improved communication between patients and clinicians about cannabis.